Planned Reductions at Point Mugu and MCB Center - James R. Faulconer:::::: (1973)
A memorandum describing a briefing session attended by Mayor Jane Tolmach and James R. Faulconer in regards to planned reductions at the Mugu and Hueneme military bases.